Get a financial life : personal finance in your twenties and thirties - Kobliner, Beth, 1965- (New York : Simon & Schuster, 2009)
From the Publisher: With 100 NEW FINANCIAL web sites! If you're like most people, you want to get your financial life in order but don't know where to begin. Since its first publication in 1996, Get a Financial Life has helped thousands of people get out of debt, start saving, and begin investing. This updated edition-expanded for the Internet age-includes the latest information on how to: Use the Web to find the best auto loans, mortgages, and credit cards. Invest in the stock market wisely and painlessly. Refinance your high-rate debt and avoid hidden fees and traps. Take advantage of the latest tax breaks-including deductions for student loans. Build a serious nest egg with long-term savings plans like the new Roth IRAs. You will also find classic, easy-to-understand advice on money basics-everything from 401(k)s to car leases, from credit reports to life insurance, from buying the right mutual funds to buying a home of your own. Whether you earn $20,000 or $200,000, Get a Financial Life will help you navigate the new world of personal finance.
Introduction -- 1: Crib Notes: Cheat Sheet For Time-Pressed Readers Who Need Help Now -- 2: Get A Grip On Your Financial Life: Figuring Out Where You Are And Where You Want To Go -- Putting a price tag on your goals -- Learning how to reach your goals -- Figuring out where your money goes -- Financial rules of thumb -- Getting your financial life in order -- Keeping track of money coming in and going out -- 3: Dealing With Debt: Finding The Cheapest Loans And Getting Yourself Out Of Hock -- Four pointers for anyone with debt -- Credit cards -- Student loans -- Car loans -- Home equity loans -- Credit reports and credit scores -- If your in serious debt -- When to consider bankruptcy -- 4: Basic Banking: How To Keep Your Costs Low And Your Money Safe -- Bank by any other name -- What to look for in a bank -- Managing your checking account -- Using the ATM wisely -- When to go internet-only -- What to do with your savings -- Joint versus separate accounts -- Warning about bank-sold investments -- 5: All You Really Need To Know About Investing: Getting A Foothold In This Rocky Landscape -- Mutual fund fundamentals -- Money market funds -- Word about inflation -- Stock funds -- Bond funds -- Right mix of investments -- Mutual fund expenses -- Deciding where to buy your mutual funds -- Socially responsible investing -- 6: Brave New World Of 401(k)s: Don't Let The Market Meltdown Be Your Excuse For Missing The Best Savings Deal Around -- What are retirement savings plan, anyway? -- How your retirement savings account works -- Contributing to your 401(k) -- Contributing to an IRA -- How to tap the money in your 401(k) or IRA if you really need it now -- Word about inflation and taxation -- Answers to some common questions -- If you're self-employed -- : Oh, Give Me A Home: New Rules For Getting A House Or Apartment Of Your Own -- 60-second explanation of the Mortgage mess -- What every renter needs to know -- Should you rent or buy? -- What lenders look for -- Real costs of owning a home -- Loans to discuss with your lender -- If you don't qualify for a mortgage -- Shopping for a mortgage -- Making the process go smoothly -- If you can't pay your mortgage -- 8: Insurance: What You Need And What You Don't: Finding The Right Policies And Skipping Coverage You Can Do Without -- Getting the best deal -- Checking out credentials -- Making the most of your employer's plans -- Health insurance -- Car insurance -- Disability insurance -- Home insurance -- Life insurance -- Insurance you probably don't need -- 9: How To Make Your Life Less Taxing: Put More Money In Your Pocket And Less In Uncle Sam's -- Why is your paycheck so small? -- Taxes you pay -- Figuring out your tax rate -- Filing your tax return -- Maximizing your tax breaks -- Making the most of your tax credits -- Ten tax moves that could save you money -- Deductions for the self-employed -- Getting your tax life in order -- Do you need a tax preparer? -- 10: Making The Most Of Military Benefits: Know What You Deserve If You Serve -- Further reading -- Special acknowledgments -- Acknowledgments -- Index.
"A Fireside book."
Includes bibliographical references and index.
Keywords: Finance, Personal; Young adults -- Finance, Personal